ON CERTAIN DIRECTIONS FOR IMPROVING THE EFFECTIVENESS OF MILITARY EDUCATION - Bauyrjan Abdumaminovich Mekambayev (Modern American Journals, 2026)
This article presents contemporary requirements for the higher education system, the outcomes of integrating pedagogical technologies into the learning process, and examines the goals, characteristics, and development trends of problem-oriented learning.
Keywords: Military education, pedagogical technologies, innovative ideas, methods and means of cognition, professional activity, creative thinking, problem-oriented learning, information technologies, self-education, and self-learning.